Analysis of Raw Water Availability for Clean Water Needs of Podomoro City Housing Tenjo, Bogor Regency - Chayati, Nurul; Lutfi, Muhamad; Insan, Muhammad Khaerul; Syaiful, Syaiful; Ramadhani, Ghinaya Hasnaa; Yosaeni, Akhmad Harish (Universitas Ibn Khaldun Bogor, 2026)
The availability of clean water in Tenjo Subdistrict, Bogor Regency, is still considered unable to meet the needs of the community. Tenjo Sub-district residents utilize Cidurian River water for various activities and daily needs, such as drinking water, irrigation of rice fields, and ponds. However, the Cidurian River often experiences bad water. Based on this, Perumda Air Minum Tirta Kahuripan Bogor Regency wants to meet the need for clean water by planning the construction of a Water Treatment Plant (IPA) in the Tenjo District area, especially Podomoro City Housing Tenjo Bogor Regency. The purpose of this research is to analyze the availability of raw water for clean water needs and planning of the clean water system of Kota Podomoro Tenjo Housing in Bogor Regency. This research uses methods with primary data collection, secondary data, and data processing with Epanet 2.0 and Excel Application programs. Then an analysis of raw water availability and clean water system planning data was carried out. The results of the analysis of raw water system planning show that the potential raw water of the Cidurian River using flo mate measuring instruments is 14,455 l / s, in stage I there are 829 SR, stage II there are 2737 SR, stage III 4555 SR are served, and the water demand from stage I to stage III reaches 31.63 l / s so that the Cidurian River can be utilized as a source of raw water for clean water services and can meet the clean water needs of Podomoro City Housing Tenjo Bogor Regency only by using 20% of Cidurian River water. The results of the hydraulic calculation analysis of piping using Epanet 2.2 obtained that each node/junction has met the hydraulic criteria.